Oligo-Miocene oxygen isotope and carbon record from IODP Site 342-U1406 - Tim E van Peer (PANGAEA, 2024)
These data contain a new high-resolution benthic foraminiferal oxygen isotope (d18Ob) record spanning ~26-22 Ma from Integrated Ocean Drilling Program Expedition 342 Site U1406 (Newfoundland Margin, Northwest Atlantic Ocean, ~40°N, 51°W; 3.8 km water depth). Oxygen isotopes of Cibicidoides mundulus (size range 125-250 micrometer) were generated using a Thermo Fisher Scientific MAT 253 mass-spectrometer coupled to a Thermo-Finnigan Kiel IV Carbonate Device in Southampton, Heidelberg, and Leipzig, and coupled to a Gasbench II in Frankfurt. International standards (NBS-18 and NBS-19) and in-house quality control standards were used to calibrate d18Ob. The record was astronomically tuned by recognising obliquity cycles in the X-ray fluorescence based CaCO3 record using newly generated coulometric carbonate content data (wt.% CaCO3), generated at the University of Southampton extquotesingles Waterfront Campus, National Oceanography Centre Southampton (UoS-NOCS), using a CM5015 coulometer equipped with an AutoMate automated analysis device